Rekonstruksi dan Visualisasi Objek 3-D Berbasis Algoritma Direct Linear Transformation - Sunu Wibirama; Risanuri Hidayat (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
Visual reconstruction and modeling of three dimensional (3-D) object is an emerging research topic in computer vision and photogrammetry fields. Nowadays, many commercial products are developed to obtain 3-D model of rigid object, starting from small ancient heritages to city landscape. Such commercial tools are very expensive and not accessible for education and research purpose. This paper aims to present a low-cost approach to generate a 3-D model from geometry of multiple two-dimensional (2-D) images using consumer-level Digital Single Lens Reflection (DSLR) camera. Direct Linear Transformation (DLT) algorithm was used to obtain 3-D point cloud. Texturization of 3-D object was generated by implementing Convex Hull and Random Sample Consensus (RANSAC) algorithms. Experimental result of small Merlion Singapore statue and large Herz-Jesu building shows that the proposed low-cost method is able to visually reconstruct small and large objects by using 10-20% feature points detected on 2D images.